Detection of incipient aqueous alteration in carbonaceous chondrites. (1st November 2022) - Krämer Ruggiu, L.; Devouard, B.; Gattacceca, J.; Bonal, L.; Leroux, H.; Eschrig, J.; Borschneck, D.; King, A.J.; Beck, P.; Marrocchi, Y.; Debaille, V.; Hanna, R.D.; et al.
Abstract: We discuss if the detection of aqueous alteration depends on the techniques that are used. We apply different methods to estimate the extent of aqueous alteration on four ungrouped carbonaceous chondrites showing limited aqueous alteration and thermal metamorphism: Chwichiya 002, El Médano (EM) 200, Northwest Africa (NWA) 12957 and NWA 11750, classified as C3 or C3.00-ung. The aim is to propose a reliable methodology to identify the most primitive chondrites. Chwichiya 002, NWA 11750 and NWA 12957 display very primitive matrices and could be amongst the most primitive chondrites currently known, similar to the least altered lithologies of the CM chondrites Paris (CM2.9) and Asuka (A) 12085 (CM2.8), A 12236 (CM2.9) and A 12169 (CM3.0). The structure of organic matter and Cr2 O3 in ferroan olivines show that the four meteorites have been less heated than the least metamorphosed standard/reference type 3 chondrite, Semarkona (LL3.00), with Chwichiya 002, NWA 12957 and NWA 11750 similar to the CO3.0 s, Acfer 094 ( C 2-ung) and Paris meteorites. Chwichiya 002 and NWA 12957 show similar alteration phases and degree of alteration, with high abundances of amorphous material with embedded metal and sulfide, resembling Glass with Embedded Metal and Sulfide (GEMS)-like materials, and tochilinite-cronstedtite intergrowths (TCIs) as the major alteration phases. The matrix in NWA 11750 contains aggregates of nanoscale olivine crystals and abundant carbonates, observed as micrometer-sized carbonate veins surrounding chondrules, and as nanoscale carbonates mixed with the fine-grained materials. It also contains abundant grains of metal and a low abundance of phyllosilicates. El Medano 200 shows a high abundance of magnetite (∼10 vol%), nanoscale phyllosilicates, troilite, and organic matter. The variability of the secondary alteration phases in the meteorites suggests different alteration mechanisms, likely depending on both the starting composition of the meteorites and the composition of the fluids of alteration. Scanning and transmission electron microscopy (SEM and TEM) allow the identification of primitive phases and the composition and spatial distribution of the secondary phases. X-ray diffraction (XRD) can detect alteration products, including some amorphous phases, although this is limited by the small coherence domains of small TCIs and other phyllosilicates. Transmission infrared (IR) spectroscopy can detect phyllosilicate and carbonate, but is ineffective for the detection of amorphous phases, metal, or sulfide. Both matrix defocused electron microprobe analyses (EMPA) and thermogravimetric analysis (TGA) allow detection of hydrated minerals, such as phyllosilicates and carbonates, but are strongly influenced by the presence of organic matter and do not reflect the overall alteration state of a meteorite. We conclude that the assessment of the primitivity of a chondrite is highly technique dependent. We propose a combination of XRD and the Cr2 O3 in ferroan olivines or Raman spectroscopy for a rapid characterization of the alteration state of a chondrite and the detection of the most primitive meteorites. Finally, the combination of XRD and TEM allows for the detection of all primary and secondary phases and represents an ideal methodology for the characterization and detailed study of primitive chondrites and the different types of incipient aqueous alteration.